Animal babies in grasslands. (Boston : Kingfisher, 2006)
Simple text and photographs describe baby animals in the grasslands and ask the reader to identify what type of animal their mothers are.
Cover title.
On board pages.
1.7
K-3
Keywords: Grassland animals -- Juvenile literature; Animals -- Infancy -- Juvenile literature; Grassland animals; Animals -- Infancy; Grassland animals; Animal babies